Nonmarital and Teen Fertility - Jason M. Fletcher; Jessica Polos (Institute of Labor Economics (IZA), 2017)
This chapter explores trends, causes and consequences of nonmarital and teen fertility in the United States and in selected European countries. First, we describe some key factors, including changes in economic institutions and family planning technologies, that likely contribute to the large changes in patterns of marriage and fertility observed in developed countries in recent decades. Secondly, we observe that substantial empirical hurdles to credibly estimating the impacts of nonmarital and teen fertility on adults' and children's outcomes remain, though recent evidence suggests more modest impacts than early evidence. Finally, we explore new directions in this research area, arguing that the conventional comparison between nonmarital and marital births should be revised to more adequately incorporate the rapidly growing number of births to cohabiting partners. Additional directions include continuing analysis of the dynamic impacts of the Great Recession and an integration of biological considerations into the economic analysis of fertility.
Keywords: J12; J13; 330; cohabitation; contraception; family economics; teen fertility; nonmarital fertility; Great Recession; genetics